Composite citations in antiquity / Volume 1 Jewish, Graeco-Roman, and early Christian uses / edited by Sean A. Adams and Seth M. Ehorn - Adams, Sean A. (Composite citations in Antiquity, 2016)
CONTENTS -- Acknowledgements -- Contributors -- Abbreviations -- Chapter 1 -- WHAT IS A COMPOSITE CITATION? AN INTRODUCTION -- Sean A. Adams and Seth M. Ehorn -- Chapter 2 -- GREEK EDUCATION AND COMPOSITE CITATIONS OF HOMER -- Sean A. Adams -- Chapter 3 -- COMPOSITE CITATIONS IN PLUTARCH -- Seth M. Ehorn -- Chapter 4 -- CITATION IN ELITE ROMAN EPISTOLARY WRITING: THE LETTERS OF CICERO, SENECA, AND PLINY -- Margaret H. Williams -- Chapter 5 -- COMPOSITE QUOTATIONS IN PHILO OF ALEXANDRIA -- James R. Royse -- Chapter 6 -- COMPOSITE QUOTATIONS IN THE DAMASCUS DOCUMENT -- Jonathan D. H. Norton -- Chapter 7 -- COMPOSITE CITATIONS IN THE SEPTUAGINT APOCRYPHA -- Sean A. Adams and Seth M. Ehorn -- Chapter 8 -- COMPOSITE CITATIONS IN JEWISH PSEUDEPIGRAPHIC WORKS: RE-PRESENTING LEGAL TRADITIONS IN THE SECOND TEMPLE PERIOD -- Garrick V. Allen -- Chapter 9 -- COMPOSITE FEATURES AND CITATIONS IN JUSTIN MARTYR'S TEXTUAL COMPOSITION -- Philippe Bobichon -- Chapter 10 -- THE TESTIMONIA HYPOTHESIS AND COMPOSITE CITATIONS -- Martin C. Albl -- Chapter 11 -- COMPOSITE CITATIONS: RETROSPECT AND PROSPECT -- Christopher D. Stanley -- Bibliography -- Index of References -- Index of Authors.